Feeding Supplementary Feeding on Baby Constipation In Bamboo Field Village - Bakara, Rizky Andriani; Rochmawati, Arva (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Constipation is a condition in which the stool hardens which makes it difficult to pass through the anus, and causes discomfort in the rectum. Babies who experience constipation are characterized by crying, whining in pain and the face turning red before defecation. The prevalence of constipation in Indonesia is very low, in Bali in children aged 4-6 years, the prevalence of constipation is 15.1%, while in children in West Padang District, Padang City, the constipation rate is 19.9 with the ratio between boys and girls is 1,2 : 1. This study aims to determine whether complementary feeding affects the occurrence of constipation in infants. This study uses a descriptive method with an exploratory approach, 30 samples with a total sampling technique, in the Ladang Bambu Village, Medan Tuntungan, with univariate data analysis. From the results of statistical analysis obtained, p = 0.02 (α = 0.05) with p < 0.05 so it can be concluded that this hypothesis failed to be rejected, namely that there was a significant effect between the provision of complementary feeding on the occurrence of constipation in children in Bamboo Farm Village. It is hoped that community services will provide counseling about MP ASI, so that babies get nutrition according to their needs and avoid constipation.